Ca2+‐dependent release of ATP from astrocytes affects herpes simplex virus type 1 infection of neurons. Issue 1 (20th August 2020) - Li Puma, Domenica Donatella; Marcocci, Maria Elena; Lazzarino, Giacomo; De Chiara, Giovanna; Tavazzi, Barbara; Palamara, Anna Teresa; Piacentini, Roberto; Grassi, Claudio
Abstract: Astrocytes provide metabolic support for neurons and modulate their functions by releasing a plethora of neuroactive molecules diffusing to neighboring cells. Here we report that astrocytes also play a role in cortical neurons' vulnerability to Herpes simplex virus type‐1 (HSV‐1) infection through the release of extracellular ATP. We found that the interaction of HSV‐1 with heparan sulfate proteoglycans expressed on the plasma membrane of astrocytes triggered phospholipase C‐mediated IP3 ‐dependent intracellular Ca 2+ transients causing extracellular release of ATP. ATP binds membrane purinergic P2 receptors (P2Rs) of both neurons and astrocytes causing an increase in intracellular Ca 2+ concentration that activates the Glycogen Synthase Kinase (GSK)‐3β, whose action is necessary for HSV‐1 entry/replication in these cells. Indeed, in co‐cultures of neurons and astrocytes HSV‐1‐infected neurons were only found in proximity of infected astrocytes releasing ATP, whereas in the presence of fluorocitrate, an inhibitor of astrocyte metabolism, switching‐off the HSV‐1‐induced ATP release, very few neurons were infected. The addition of exogenous ATP, mimicking that released by astrocytes after HSV‐1 challenge, restored the ability of HSV‐1 to infect neurons co‐cultured with metabolically‐inhibited astrocytes. The ATP‐activated, P2R‐mediated, and GSK‐3‐dependent molecular pathway underlying HSV‐1 infection is likely shared by neurons and astrocytes, given that the blockade of either P2Rs or GSK‐3 activation inhibited infection of both cell types. These results add a new layer of information to our understanding of the critical role played by astrocytes in regulating neuronal functions and their response to noxious stimuli including microbial agents via Ca 2+ ‐dependent release of neuroactive molecules. Main Points: Ca 2+ ‐dependent release of ATP from astrocytes affects neurons' vulnerability to HSV‐1 infection P2R‐dependent GSK‐3 activation is involved in HSV‐1 entry/replication in both astrocytes and neurons